2022
DOI: 10.3389/fenvs.2022.1042400
|View full text |Cite
|
Sign up to set email alerts
|

CEO educational attainment, green innovation, and enterprise performance: Evidence from China’s heavy-polluting enterprises

Abstract: Our study explores how CEOs’ educational attainment affects green innovation at the enterprise level and whether CEO educational attainment and green innovation can improve enterprise performance. To date, few studies have used environmental patents of listed companies to measure green innovation at the micro-level. Furthermore, existing studies have rarely considered the heterogeneity of the enterprise type or social responsibility and institutional intervention. Thus, by using a fixed-effects model, we argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…Specifically, business owners with a university degree have a product innovation probability of 33.8%, which is higher than that of those without formal training at 11.8%. Similar conclusions have been drawn in several studies conducted in different countries, indicating that businesses owned by individuals with higher levels of education have a greater potential for innovative and creative advancements [33].…”
Section: Empirical Model Estimation 421 the Results Of The Samplesupporting
confidence: 88%
“…Specifically, business owners with a university degree have a product innovation probability of 33.8%, which is higher than that of those without formal training at 11.8%. Similar conclusions have been drawn in several studies conducted in different countries, indicating that businesses owned by individuals with higher levels of education have a greater potential for innovative and creative advancements [33].…”
Section: Empirical Model Estimation 421 the Results Of The Samplesupporting
confidence: 88%
“…Exploring the multifaceted roles of MSII in the green governance of heavily polluting industries is vital, particularly when addressing the trifecta of challenges these industries face: inadequate environmental investment resources, governance motivation deficits, and technological and innovation obstacles (Du et al, 2023; Guo et al, 2023; Zhang, Li, et al, 2022). The influence of MSII on these areas is crucial to determining its potential for environmental impact.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Research offers two perspectives on MSII's governance effects on environmental performance. Positively, from the diminishing marginal cost of governance viewpoint, MSII can supervise and incentivize management, curtailing the tunneling activities of major shareholders and resolving the issues of resource scarcity and motivational inadequacies in green governance, thereby enhancing environmental outcomes (Tang et al, 2023; Zhang, Li, et al, 2022). Additionally, leveraging its social network, MSII may facilitate the dissemination of innovative knowledge, helping to overcome the technical barriers in green governance (Du et al, 2023).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The background characteristics of CEOs deeply affect the disclosure of the environmental management information of heavily polluting enterprises. It was found that CEOs’ education significantly influenced the environmental management information disclosure of the firm and significantly improved the firm's performance (C. Zhang, Li, Gou, et al, 2022). CEOs’ overseas experience had a significant positive effect on environmental management information disclosure, more significantly in state‐owned heavily polluting firms (Hussain et al, 2022).…”
Section: Literature Analysis and Research Hypothesismentioning
confidence: 99%